Two Kemsky Wooden Worship Crosses of the Middle 17th Century - Antropova, Irina A.; Zhuravleva, Anastasia I.; Maksimenko, Zhanna A. (Actual Problems of Theory and History of Art, 2023)
The article is dedicated to two little-known wooden Crucifixes from the mid-17th century, rare in their artistic and iconographic characteristics. Both crosses are now in the Kemsky Assumption Cathedral. The authors conducted comprehensive historical, art-historical and scientific research, which introduced new archival documents into scientific circulation, as well as a large amount of data on the materials and structure of the monuments. On the basis of all the data, we assume that the crosses examined could have been made by different masters who used the same technological and iconographic tradition.
Keywords: Kem; Assumption Cathedral; cross; Crucifixion; carving; polychrome painting